2007
DOI: 10.1080/01635580701413934
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene and Soy Isoflavones in the Treatment of Prostate Cancer

Abstract: Dietary intake of lycopene and soy has been associated with a lower risk of prostate cancer. In vitro studies with lycopene and genistein, a soy isoflavone, have shown induction of apoptosis and inhibition of cell growth in androgen-sensitive (LNCaP) and androgen-independent (PC3 and VeCaP) prostate cancer cell lines. In a previous Phase II clinical trial in prostate cancer patients, we observed prostate-specific antigen (PSA) stabilization with soy isoflavone intake. In this Phase II clinical trial, we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
105
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(109 citation statements)
references
References 64 publications
0
105
1
3
Order By: Relevance
“…35 of 37 (95%) evaluable patients in the lycopene group and 22 of 33 (67%) evaluable patients in the lycopene plus soy isoflavone group achieved stable disease, described as stabilization in serum PSA level. The data suggest that lycopene and soy isoflavones have activity in prostate cancer patients with PSA relapse disease and may delay progression of both hormone-refractory and hormone-sensitive prostate cancer [145]. Another human in vivo study also showed that a daily diet containing four slices of a bread rich in heat treated soy grits favorably influences the PSA level and the free/total PSA ratio in patients with prostate cancer, suggesting the inhibitory effects of phytoestrogen on PSA level [146].…”
Section: Clinical Trials: Effects On Patients With Prostate Cancermentioning
confidence: 83%
See 1 more Smart Citation
“…35 of 37 (95%) evaluable patients in the lycopene group and 22 of 33 (67%) evaluable patients in the lycopene plus soy isoflavone group achieved stable disease, described as stabilization in serum PSA level. The data suggest that lycopene and soy isoflavones have activity in prostate cancer patients with PSA relapse disease and may delay progression of both hormone-refractory and hormone-sensitive prostate cancer [145]. Another human in vivo study also showed that a daily diet containing four slices of a bread rich in heat treated soy grits favorably influences the PSA level and the free/total PSA ratio in patients with prostate cancer, suggesting the inhibitory effects of phytoestrogen on PSA level [146].…”
Section: Clinical Trials: Effects On Patients With Prostate Cancermentioning
confidence: 83%
“…Recently, the investigators from our institute reported the results from a phase II clinical trial designed to investigate the efficacy of lycopene alone or in combination with soy isoflavones on serum PSA levels in men with prostate cancer [145]. 35 of 37 (95%) evaluable patients in the lycopene group and 22 of 33 (67%) evaluable patients in the lycopene plus soy isoflavone group achieved stable disease, described as stabilization in serum PSA level.…”
Section: Clinical Trials: Effects On Patients With Prostate Cancermentioning
confidence: 99%
“…Two studies on gene-enviroment interaction in relation to PCa showed the importance of dietary composition 12,13 . Of nutraceuticals, phytoceuticals and complex plant extracts or a combination of them, lycopene 14 , soy flavonoids 15 , silibinin 16 and preparations of soy and a combination of other supplements including vitamin E, selenium, lycopene and silymarin have been tested in human clinical trials (reviewed in ref. 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…This combination inhibited the growth of androgen-responsive prostate cancer cells (LNCaP) as well as androgen-independent metastatic prostate cancer cells (DU-145) and PC-3 prostate cancer cells by both estrogen dependent and independent pathways and by stimulation of caspase-3 activity. A phase two clinical trial by Vaishampayan et al [73] investigated the efficacy of lycopene alone or in combination with soy isoflavones on serum PSA in men with prostate cancer who had rising serum PSA status-post local therapy or while on hormone therapy (n=71). The authors concluded that there was no decline in serum PSA level in either group and that there was no additive effect with both compounds.…”
Section: Human Trials Of Phytoestrogens and Prostate Health And Diseasementioning
confidence: 99%